2022
DOI: 10.1155/2022/2916700
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment and Impacts of Chronic Sinusitis with the Confluence of Biyuan Tongqiao Granules and Saline Nasal Irrigation

Abstract: In this research study, we will study the clinical effect of Biyuan Tongqiao granules with saline nasal irrigation for treatment of chronic sinusitis. It will also study its impacts on the computed tomography (CT) score of the nasal sinus and negative reactions in patients. For this purpose, ninety (90) patients with chronic sinusitis were admitted to the hospital (June 2019 to June 2020). They were selected as the research subjects and divided into experimental and control groups randomly with 45 cases in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…More and more clinical trials have evaluated the effect of TCM nasal rinse on CRS recovery after ESS, indicating that it may be an effective and safe treatment method. Studies have revealed that [20][21][22][23][24] local nasal irrigation with TCM is effective in reducing nasal mucosa edema, promoting epithelialization of surgical cavity mucosa, and promoting the recovery of nasal mucociliary structure and motor function. Moreover, the local action mechanism of TCM is not a single antibacterial and anti-inflammatory, but also related to local immune regulation.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…More and more clinical trials have evaluated the effect of TCM nasal rinse on CRS recovery after ESS, indicating that it may be an effective and safe treatment method. Studies have revealed that [20][21][22][23][24] local nasal irrigation with TCM is effective in reducing nasal mucosa edema, promoting epithelialization of surgical cavity mucosa, and promoting the recovery of nasal mucociliary structure and motor function. Moreover, the local action mechanism of TCM is not a single antibacterial and anti-inflammatory, but also related to local immune regulation.…”
Section: Plos Onementioning
confidence: 99%
“…Before and after treatment, the patient’s liver and kidney functions were normal. Only a few patients experienced nasal pain, nasal itching, and headache during nasal irrigation [ 24 – 26 ]. A systematic review published in 2011 showed the effectiveness and safety of TCM nasal irrigation for the postoperative recovery of chronic sinusitis after ESS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%